Modification of cycling biomechanics during a swim-to-cycle trial - Delextrat, A.; Tricot, V.; Bernard, T.; Vercruyssen, F.; Hausswirth, C.; Brisswalter, J. (Journal of Applied Biomechanics, 2005)
The aim of this study was to investigate the effects of drafting, i.e., swimming directly behind a competitor, on biomechanical adaptation during subsequent cycling. Eight well-trained male triathletes underwent three submaximal sessions in a counterbalanced order. These sessions comprised a 10-min ride on a bicycle ergometer at 75% of maximal aerobic power (MAP) at a freely chosen cadence. This exercise was preceded either by a 750-m swim performed alone at competition pace (SCA trial: swimming-cycling alone), a 750-m swim in a drafting position at the same pace as during SCA (SCD trial: swimming-cycling with drafting), or a cycling warm-up at 30% of MAP for the same duration as the SCA trial (CTRL trial). The results indicated that the decrease in metabolic load when swimming in a drafting position (SCD trial) was associated with a significantly lower pedal rate and significantly higher mean and peak resultant torques when compared to the SCA trial, p < 0.05. These results could be partly explained by the lower relative intensity during swimming in the SCD trial when compared with the SCA trial, involving a delayed manifestation of fatigue in the muscles of the lower limbs at the onset of cycling.